Engineered Zinc Finger Protein Targeting 2LTR Inhibits HIV Integration in Hematopoietic Stem and Progenitor Cell-Derived Macrophages: In Vitro Study - Koollawat Chupradit; Wannisa Khamaikawin; Supachai Sakkhachornphop; Chaniporn Puaninta; Bruce E. Torbett; Suparerk Borwornpinyo; Suradej Hongeng; Methichit Wattanapanitch; Chatchai Tayapiwatana (International Journal of Molecular Sciences, 2022)
HSPC-based gene therapy for AIDS patients.
Keywords: HIV Research and Treatment; RNA Interference and Gene Delivery; Virus-based gene therapy research